Prediction of ICRF minority heating schemes for JET D–T experiments. (1st December 2022) - Gallart, D; Mantsinen, M J; Manyer, J; Planas, E; Taylor, D M A; Garcia, J; Frigione, D; Garzotti, L; Kim, Hyun-Tae; Nocente, M; Rimini, F; Van Eester, D; et al.
Abstract: Achieving high-performance conditions and maximizing the fusion yield of plasma discharges have been one of the main goals of recent Joint European Torus (JET) campaigns in preparation for its second deuterium–tritium (D–T) campaign. The simulations shown in this work delve into the role of external heating using neutral beam injection (NBI) and radio-frequency waves in the ion cyclotron range of frequencies (ICRF) in order to optimise high fusion performance in the JET tokamak. A baseline discharge with record neutron rate is used as a reference in order to perform a D–T prediction, which considers the NBI+RF synergy. In this work, our focus is on JET's two main minority schemes, H and 3 He. This study tackles the heating mechanisms by which these schemes reach high-performance conditions. The H scheme typically boosts the ICRF fusion enhancement through the second D harmonic heating, whereas 3 He minority is characterised by its strong bulk ion heating. Both features are beneficial for increasing the fusion yield. Nevertheless, the minority concentration is a relevant parameter, which needs to be assessed to understand in which concentration ranges the benefits of each particular minority scheme are met. Therefore, the main objective of this work is to assess in which concentration range the ICRF fusion enhancement and bulk ion heating are optimal, for H and 3 He, respectively. Under these conditions, our prediction suggests 3 He concentration should stay above 1.2% and H should remain below 2.2%.